2016
DOI: 10.1007/s00418-016-1467-y
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization coefficients evaluating the distribution of molecular targets in microscopy methods based on pointed patterns

Abstract: and super-resolution structured illumination microscopy. The similar tendency of the values obtained using different colocalization approaches suggests the biological validity of the scientific conclusions. The presented methodology represents a good basis for further development of the quantitative analysis of immunoelectron microscopy data and can be used for studying molecular interactions at the ultrastructural level. Moreover, this methodology can be applied also to the other super-resolution microscopy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Moreover, our novel immunoelectron microscopy studies showed these molecules localize to the triad. To our knowledge, this is the first report on ultrastructural localization of PI3P, PI(3,4)P2 and PI (4,5)P2 at the triad in a vertebrate model, as previous studies focused on culture cell lines [40][41][42][43][44]. Our data add to the growing evidence showing the importance of PIP metabolism in the development and maintenance of this key muscle substructure.…”
Section: Plos Onesupporting
confidence: 66%
“…Moreover, our novel immunoelectron microscopy studies showed these molecules localize to the triad. To our knowledge, this is the first report on ultrastructural localization of PI3P, PI(3,4)P2 and PI (4,5)P2 at the triad in a vertebrate model, as previous studies focused on culture cell lines [40][41][42][43][44]. Our data add to the growing evidence showing the importance of PIP metabolism in the development and maintenance of this key muscle substructure.…”
Section: Plos Onesupporting
confidence: 66%
“…To facilitate the visualisation of 6 nm gold nanoparticles in images, Adobe Photoshop CS3 Version 10.0 was used to cover the small nanoparticles co-centrically with red dots. To evaluate computationally the spatial distribution and quantitative mutual dependence of the nanoparticles in electron microscopy images, we developed and used the quantitative objective approach (Pastorek et al, 2016), based on the previously published method describing a pair cross-correlation function (PCCF) (Philimonenko et al, 2000). In this study, we used a newly developed plugin (Pastorek et al, 2016) on the Fiji software platform to quantify the relative colocalisation coefficient (RCC).…”
Section: Temmentioning
confidence: 99%
“…To evaluate computationally the spatial distribution and quantitative mutual dependence of the nanoparticles in electron microscopy images, we developed and used the quantitative objective approach (Pastorek et al, 2016), based on the previously published method describing a pair cross-correlation function (PCCF) (Philimonenko et al, 2000). In this study, we used a newly developed plugin (Pastorek et al, 2016) on the Fiji software platform to quantify the relative colocalisation coefficient (RCC). In summary, we analysed 21 cells co-labelled for NM1 and PtdIns(4,5)P 2 , 59 control cells and 213 α-amanitin-treated cells colabelled for BrRNA and PtdIns(4,5)P 2 , 37 cells co-labelled for RNA and PtdIns(4,5)P 2 , 20 cells co-labelled for cholesterol and PtdIns(4,5)P 2 , and 41 cells co-labelled for ceramide and PtdIns(4,5)P 2 .…”
Section: Temmentioning
confidence: 99%
“…Moreover, our novel immunoelectron microscopy studies showed these molecules localize to the triad. To our knowledge, this is the first report on ultrastructural localization of PI3P, PI(3,4)P2 and PI(4,5)P2 at the triad in a vertebrate model, as previous studies focused on culture cells (Watt et al, 2002) (Tabellini et al, 2003) (Mayhew et al, 2004) (Wegner et al, 2014) (Pastorek et al, 2016). Our data add to the growing evidence showing the importance of PIP metabolism in the development and maintenance of this key muscle substructure.…”
Section: Discussionmentioning
confidence: 86%